Veterinary-sanitary inspection of cattle meat affected with benign tumor - Ivan G Seregin; Evgeniya S Baranovich; Vladimir E Nikitchenko; Dmitry V Nikitchenko; Ekaterina O Rystsova (RUDN Journal of Agronomy and Animal Industries, 2019)
The rate of benign tumor detection in slaughtered cattle was studied. Tumor pathology was detected on average in 0.04% of the studied livestock. Manifestations of various new growths in this animal species have specific features. Tumors are detected 2-3 times more often in cows and bulls than in young animals. The veterinary and sanitary characteristics of cattle meat affected with benign tumors were compared with those of animal meat without tumors. Affected meat had deviations in physical properties, chemical composition of meat affected with tumors, content of primary protein breakdown products, volatile fatty acids (+0.05 mg/KOH) and amino-ammonium nitrogen (+0.54 mg/%) compared with meat of healthy cattle. It was revealed that the samples of meat affected with tumors were highly contaminated with microorganisms (0.28…0.80×102), including coliforms and St. aureus . Pathogenic bacteria of the genera Salmonella , L. monocytogenes , Cl. perfringens etc. were not detected in the test samples. In meat affected with tumors, relative bioavailability decreased by 4.99…13.87% and safety - by 5.89…13.89% as compared to meat of healthy cattle. Based on the data obtained, proposals were developed on the most rational and safe use of meat from animals affected by benign tumors for food and feed.